Clinical characteristics and outcomes of young adults with first myocardial infarction: Results from Gulf COAST. (December 2020) - Alfaddagh, Abdulhamied; Khraishah, Haitham; Rashed, Wafa; Sharma, Garima; Blumenthal, Roger S; Zubaid, Mohammad
Highlights: CVD risk factors are common in young Gulf-Arabs presenting with first AMI. Older AMI patients receive less potentially lifesaving therapies than young adults. In-hospital adverse CVD events and mortality were low in young adults with AMI. Mortality up to 12-months post-AMI was lower in young adults than in older adults. Abstract: Introduction: Limited data exists on the risk factor profile and outcomes of young patients suffering their first acute myocardial infarction (AMI). Methods: We examined 1562 Gulf-Arabs without prior cardiovascular disease presenting with first AMI enrolled in the Gulf COAST prospective cohort. Clinical characteristics were compared in patients ≤50 years of age (young) vs. >50 years (older). Associations between age group and in-hospital adverse events (re-infarction, heart failure, cardiogenic shock, cardiac arrest, stroke, and in-hospital death) or post-discharge mortality were estimated using logistic regression. Results: Young patients represented 26.1% (n = 407) of first AMI cases and were more likely to be men (82.8% vs. 66.5%), current smokers (49.9% vs 19.0%), obese (38.3% vs 28.0%), and have family history of premature coronary artery disease (21.4% vs 10.4%) compared with older patients (all P < 0.001). Young patients were more likely to receive β-blockers (83.0% vs 74.4%; P < 0.001), clopidogrel (82.3% vs 76.0%; P = 0.009) and primary reperfusion therapy (85.6% vs. 75.6%; P = 0.003). Young adults had lower in-hospital death (adjusted odds ratio [aOR] = 0.37; 95%CI = 0.16–0.86) or any in-hospital adverse cardiovascular events (aOR = 0.53; 95%CI = 0.34–0.83). Young adults had lower likelihood of cumulative death at 12-month post-discharge (aOR = 0.34; 95%CI = 0.19–0.59) after adjusting for potential confounders. Conclusion: Young patients with first AMI were more likely to be obese, smokers and have family history of premature coronary artery disease compared to older adults. Young patients were more likely to receive guideline-proven therapies and have better in-hospital and post-discharge mortality. These data highlight important age-related care gaps in patients suffering AMI for the first time.